Transverse and Quantum Localization of Light: A Review on Theory and Experiments - Giordani, Taira; Schirmacher, Walter; Ruocco, Giancarlo; Leonetti, Marco (Frontiers in Physics, 2021)
Anderson Localization is an interference effect yielding a drastic reduction of diffusion of wave packets such as sound, electromagnetic waves, and particle wave functions in the presence of strong disorder. In optics, this effect has been observed and demonstrated unquestionably only in dimensionally reduced systems. In particular, transverse localization (TL) occurs in optical fibers, which are disordered rectangular to, and translationally invariant along, the propagation direction, where the resonant and tube-shaped localized states act as micro-fiber-like single-mode transmission channels. Since the proposal of the first TL models in the early eighties, the fabrication technology and experimental probing techniques, took giant steps forwards: TL has been observed in photorefractive crystals, in plastic optical fibers, and also in glassy platforms, while employing direct laser writing, it is now possible to tailor and design disorder. This review covers all these aspects that are today making TL closer to applications such as quantum communication or image transport. We first discuss nonlinear optical phenomena in the TL regime, enabling steering of optical communication channels. Then we report on experiments concerning the nature of the transversally localized states, showing a behavior of the localization strength with wavelength unexpected by the traditional theoretical model. We present a new consistent theoretical approach capable of describing all aspects of TL. Finally, we report on some quantum aspects, showing how a single-photon state can be localized in some of its inner degrees of freedom and how quantum phenomena can be employed to secure a quantum communication channel.